(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2010)
A Simple RP-HPLC method with UV detection has been validated to determine omeprazole concentrations in human serum and urine samples. The mobile phase consisted of a mixture of potassium dihydrogen phosphate buffer (pH 7.2 ± 0.05; 0.2 M) and acetonitrile (70:30, v/v), pumped at a flow rate of 1.0 ml/min through the C-8 column at room temperature. Peaks were monitored by UV absorbance at 302 nm at a sensitivity of 0.0001. The developed method was selective and linear for omeprazole concentrations ranging between 5 to 1000ng/ml for serum samples and 1 to 100μg/ml for urine samples. The recovery of omeprazole ranged from 95.68 to 99% and 95.54 to 99.8% for the serum and urine samples respectively. The limit of quantitation (LOQ) of omeprazole was 5 ng/ml. The intraday accuracy ranged from 93.54 to 104.38% and 100.55 to 103.48% for the serum and urine respectively. The interday accuracy varied from 97.61 to 113.95% and 97.42 to 109.97% for the serum and urine respectively. For the LOQ, good values of precision (6.03 and 10.13% for intraday and interday, respectively) were also obtained. Acceptable results were obtained during stability study. This method proved to be simple, accurate and precise for pharmacokinetic and bioequivalence studies of omeprazole. Key words: Omeprazole; RP-HPLC; Method validation. DOI: 10.3329/dujps.v8i2.6026 Dhaka Univ. J. Pharm. Sci. 8(2): 123-130, 2009 (December)